Performance Pay and Multiple Tasks; Inner Motivations and Participation Constraints - Grepperud, Sverre; Pedersen, Pål Andreas (Journal of Applied Business and Economics, 2022)
In principal-agent relationships, agents are often engaged in several tasks. Contracts are studied under different participation constraints for an agent that receives non-pecuniary rewards. The optimal contracts vary according to the degree of dependency between the efforts, the strength and distribution of inner motivations, and, the type of constraint. If the inner motivation for the incentivized task is relatively high (low), the inner motivation for non-incentivized tasks is relatively low (high) and/or the degree of substitutability between the efforts is relatively low (high), the bonus where a utility constraint holds, is higher (lower) than when a net-income constraint holds.